2021
DOI: 10.21203/rs.3.rs-916612/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic landscape of canine diffuse large B-cell lymphoma identifies distinct subtypes with clinical and therapeutic implications

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoid neoplasm in dogs, being characterized by a remarkable degree of clinical heterogeneity not completely explained by molecular data. This poses a major barrier to understanding the disease and response to therapy or when using dogs with DLBCL in clinical trials. We performed an integrated analysis of genome, exome and RNA sequencing in a cohort of 77 canine DLBCL to define the genetic landscape of this tumor. A wide range of signaling pathways and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Subsequent studies revealed that deletions and inactivating mutations of TRAF3 are frequently detected in many other types of mature B cell malignancies, including diffuse large B-cell lymphoma (DLBCL), splenic marginal zone lymphoma (MZL), B-cell chronic lymphocytic leukemia (B-CLL), mantle cell lymphoma (MCL), Waldenström's macroglobulinemia, and Hodgkin lymphoma (HL) (1,3,(9)(10)(11)30). This is corroborated by frequent TRAF3 mutations detected in canine non-Hodgkin lymphomas (NHL) (31)(32)(33)(34). Similar to Traf3 -/mouse B cells, human B cells with germline TRAF3 mutations that reduce TRAF3 expression also exhibit constitutive NF-kB2 activation and enhanced responses to BCR, BAFF, TLR9, and IL-6 signaling, including increased proliferation and plasma cell formation associated with elevated activation of NF-kB1, ERK, AKT, and STAT3 (14).…”
Section: Traf3 In B Cell Biology and B Cell Malignanciesmentioning
confidence: 87%
“…Subsequent studies revealed that deletions and inactivating mutations of TRAF3 are frequently detected in many other types of mature B cell malignancies, including diffuse large B-cell lymphoma (DLBCL), splenic marginal zone lymphoma (MZL), B-cell chronic lymphocytic leukemia (B-CLL), mantle cell lymphoma (MCL), Waldenström's macroglobulinemia, and Hodgkin lymphoma (HL) (1,3,(9)(10)(11)30). This is corroborated by frequent TRAF3 mutations detected in canine non-Hodgkin lymphomas (NHL) (31)(32)(33)(34). Similar to Traf3 -/mouse B cells, human B cells with germline TRAF3 mutations that reduce TRAF3 expression also exhibit constitutive NF-kB2 activation and enhanced responses to BCR, BAFF, TLR9, and IL-6 signaling, including increased proliferation and plasma cell formation associated with elevated activation of NF-kB1, ERK, AKT, and STAT3 (14).…”
Section: Traf3 In B Cell Biology and B Cell Malignanciesmentioning
confidence: 87%